Stable Isotope Fractionation Caused by Glycyl Radical Enzymes during Bacterial Degradation of Aromatic Compounds - Morasch, Barbara (American Society for Microbiology, 2004)
Stable isotope fractionation was studied during the degradation of m-xylene, o-xylene, m-cresol, and p-cresol with two pure cultures of sulfate-reducing bacteria. Degradation of all four compounds is initiated by a fumarate addition reaction by a glycyl radical enzyme, analogous to the well-studied benzylsuccinate synthase reaction in toluene degradation. The extent of stable carbon isotope fractionation caused by these radical-type reactions was between enrichment factors (ɛ) of −1.5 and −3.9‰, which is in the same order of magnitude as data provided before for anaerobic toluene degradation. Based on our results, an analysis of isotope fractionation should be applicable for the evaluation of in situ bioremediation of all contaminants degraded by glycyl radical enzyme mechanisms that are smaller than 14 carbon atoms. In order to compare carbon isotope fractionations upon the degradation of various substrates whose numbers of carbon atoms differ, intrinsic ɛ (ɛ(intrinsic)) were calculated. A comparison of ɛ(intrinsic) at the single carbon atoms of the molecule where the benzylsuccinate synthase reaction took place with compound-specific ɛ elucidated that both varied on average to the same extent. Despite variations during the degradation of different substrates, the range of ɛ found for glycyl radical reactions was reasonably narrow to propose that rough estimates of biodegradation in situ might be given by using an average ɛ if no fractionation factor is available for single compounds.